Development of Bupena-Based Test Instruments on the Theme of Care about Living Things - Srie Faizah Lisnasari; Rita Herlina Br PA; Pandapotan Tambunan; Renato Gema Nugraha Hutabarat; Hotma Tiolina Siregar; Irwansyah Irwansyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
It is still necessary to develop the instruments in the Authentic Assessment Book (BUPENA) used by students because the condition of the questions contained in the current BUPENA are unable to find problems, are not related to everyday life and the questions are very easily accessible. The answer from the internet. This study aims to (1) determine the validity of the development of BUPENA-based test instruments on the theme of Caring for Living Creatures (2) to determine the effectiveness of BUPENA-based test instruments on the theme of Caring for Living Creatures. The development is carried out using the ADDIE model which consists of Analysis, Design, Development, Implementation, and Evaluation. The test instrument developed is in the form of questions related to student life. The validity of the test instrument was carried out by 4th grade elementary school lecturers and teachers. The results showed that the BUPENA-based test instrument on the theme of Caring for Living Creatures was valid and feasible as evidenced by the validation process carried out by the validator on a 10-item questionnaire. The results from the first validator obtained 84.7%, from the second validator the results obtained 87.5%, and from the third validator 94%. Measurement of the effectiveness of the test instrument product obtained a value of 77% in the effective category. The conclusion of the development of the BUPena-based test instrument is declared valid and effective